Embracing Global Computing in Emerging Economies : First Workshop, EGC 2015, Almaty, Kazakhstan, February 26-28, 2015, proceedings /: First Workshop, EGC 2015, Almaty, Kazakhstan, February 26-28, 2015, proceedings. (2015) - Unknown
No abstract available